In vivo sentinel lymph node identification using fluorescent tracer imaging in colon cancer: A systematic review and meta-analysis. (February 2021) - Burghgraef, T.A.; Zweep, A.L.; Sikkenk, D.J.; van der Pas, M.H.G.M.; Verheijen, P.M.; Consten, E.C.J.
Graphical abstract: Abstract: Introduction: The use of fluorescence might improve the performance of the sentinel lymph node procedure in patients with colon cancer. This systematic review was conducted to gain insight in the performance and applicability of the sentinel lymph node procedure using fluorescence. Method: A systematic literature search was performed. Databases were searched for prospective studies concerning sentinel node identification using fluorescence in colon cancer. Detection rate, accuracy rate and sensitivity of the sentinel lymph node procedure were calculated for early stage (T1-T2) and more invasive (T3-T4) tumours. Results: Analyses of five included studies showed for respectively T3-T4 and T1-T2 tumours a detection rate of 90 % and 91 %, an accuracy rate of 77 % and 98 %, and a sensitivity of 30 % and 80 %. Conclusion: The sentinel lymph node procedure using fluorescence in early stage (T1-T2) colon cancer seems to be promising. Larger cohorts are necessary to confirm these results.